Flow visualization and analytical study on the exhaust gas diffusion of a frigate - Dobrucali, Erinc (Array, 2021)
Wind tunnel flow visualization tests were conducted to analyse the efflux velocity impacts and the yaw angle on the smoke dispersion of the exhaust for a generic frigate. An analytical study was also implemented to obtain the exhaust plume trajectories. The 1/100 scale generic frigate, having a platform for helicopters on the aft of the ship, was built and employed during the experimental study. The forward and astern cruises of the frigate were considered. It is found that the plume height and the exhaust gases momentum increase with the velocity ratio. The problem of smoke nuisance was observed for the ratios with low velocity such as K=0.2. The plume was also directed towards the helicopter platform when the yaw angles are higher than 10°. The experimental results are compared with the analytical solutions for three different velocity ratios.